2015
DOI: 10.1155/2015/127820
|View full text |Cite
|
Sign up to set email alerts
|

Dual Circularly Polarized Omnidirectional Antenna with Slot Array on Coaxial Cylinder

Abstract: A dual circularly polarized (CP) omnidirectional antenna based on slot array in coaxial cylinder structure is presented in this paper. It is constructed by perpendicular slot pairs around and along the axis of the coaxial cylinder to realize the omnidirectional CP property, and two ports are assigned in its two sides as left hand circularly polarized (LHCP) port and right hand circularly polarized (RHCP) port, respectively. The proposed antenna achieves a bandwidth of 16.4% ranging from 5.05 to 5.95 GHz with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…This choice facilitates a good balance of the RHCP and LHCP power radiated by each of the four rings of slot pairs. Thus, the power radiated by the system in the horizontal direction has a high directivity [15]. Note that this DCPOA is a traveling wave antenna with good isolation between the RHCP and LHCP ports and thus achieves very good polarization diversity.…”
Section: Dcpoa Parametric Study and Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…This choice facilitates a good balance of the RHCP and LHCP power radiated by each of the four rings of slot pairs. Thus, the power radiated by the system in the horizontal direction has a high directivity [15]. Note that this DCPOA is a traveling wave antenna with good isolation between the RHCP and LHCP ports and thus achieves very good polarization diversity.…”
Section: Dcpoa Parametric Study and Analysismentioning
confidence: 99%
“…This feature can overcome de-polarization, improve the stability of the channel, and increase the capacity of the communications. It has been demonstrated that the OCPSA has dual-CP omnidirectional radiation performance when it is upright and fed from its top port or its bottom ports [15]. However, the feed cable to the top port was originally hung on the side of the antenna and, as a consequence, broke the omnidirectional pattern and deteriorated the CP performance in practice.…”
Section: Tfs-fed Improved Dual Cp Omnidirectional Antennamentioning
confidence: 99%
See 3 more Smart Citations